A Noise Monitoring System Used for Substation Boundary: Part 2 -- Noise Evaluation Method of Multi-Measuring Points. Issue 2 (June 2020) - Li, Shiping; Hou, Guoyan; Wang, Jian; Lan, Xinsheng; Tang, Ming; Zhou, Yiqian; Liu, Tao; Liu, Hongzhi
Abstract: After the noise monitoring system of substation boundary is deployed, the monitoring platform can obtain a large number of original noise data. How to deal with the noise monitoring data and give the specific indicators to evaluate the noise radiation level need further analysis. In this paper, the distribution of long-term noise monitoring sequence values is discussed by means of noise distribution probability fitting. Seven mainstream distribution fitting functions are compared and analyzed, and it is found that burr distribution has better performance. The final evaluation mean value is given by the three parameters Burr distribution.